Sex differences in cognitive decline among middle-aged and older adults: a cohort study in Europe - Wolfova, Katrin; Frycova, Barbora; Seblova, Dominika; Tom, Sarah; Skirbekk, Vegard Fykse; Brennan Kearns, Pavla (Age and ageing, 2024)
Previous studies on sex differences in cognitive decline provide inconsistent findings, with many European countries being underrepresented. We determined the association between sex and cognitive decline in a sample of Europeans and explored differences across birth cohorts and regions. Participants 50+ years old enrolled in the Survey of Health, Ageing and Retirement in Europe had their cognition measured by tests of immediate recall, delayed recall and verbal fluency biennially up to 17 years of follow-up (median 6, interquartile range 3-9 years). We used linear mixed-effects models to assess the relationship between sex and the rate of cognitive decline, adjusting for sociodemographic and health-related characteristics. Of 66,670 participants (mean baseline age 63.5 ± standard deviation 9.4), 55% were female. Males and females had similar rates of decline in the whole sample in immediate recall (beta for interaction sex × time B = 0.002, 95% CI -0.001 to 0.006), delayed recall (B = 0.000, 95% CI -0.004 to 0.004), and verbal fluency (B = 0.008, 95% CI -0.005 to 0.020). Females born before World War II had a faster rate of decline in immediate recall and delayed recall compared to males, while females born during or after World War II had a slower rate of decline in immediate recall. Females in Central and Eastern Europe had a slower rate of cognitive decline in delayed recall compared to males. Our study does not provide strong evidence of sex differences in cognitive decline among older Europeans. However, we identified heterogeneity across birth cohorts and regions.